Rape in the Nordic Countries: Continuity and Change - Heinskou, Marie Bruvik; Skilbrei, May-Len; Stefansen, Kari (Routledge Research in Gender and Society, 2019)
The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/9780429467608, has been made available under a Creative Commons Attribution-NonCommercial-No Derivatives 4.0 license. While the Nordic countries are listed at the top in most international rankings of gender equality and citizens’ feelings of security, studies on the prevalence of sexual victimisation present a different picture, suggesting that the very countries that have invested much in establishing gender equality actually see a high prevalence of sexual violence. This book sheds light on the phenomenon and construction of rape and other forms of sexual violence within the Nordic region, exploring the ways in which rape and sexual violence are dealt with through criminal law and considering governmental policies aimed at combatting it, with a special focus on legal regulations and developments. Thematically organised, it offers new research on perpetrators, victimhood, criminal justice and prevention. Multi-disciplinary in approach, it brings together the latest work from a range of scholars to offer insights into the situation in the five Nordic countries, asking how and why rape and other forms of sexual violence occur, whilst also addressing the timely issues of online sexual cultures, BDSM and the grey areas of sexual offences. As such, it will appeal to scholars of sociology, criminology and law with interests in gender and sexual violence.